Gut and oral microbial compositional differences in women with breast cancer, women with ductal carcinoma in situ, and healthy women - Emma McCune; Anukriti Sharma; Breanna Johnson; Tess O'Meara; Sarah Theiner; Maribel Campos; Diane Heditsian; Susie Brain; Jack A. Gilbert; Laura Esserman; Michael J. Campbell (mSystems)
ABSTRACT This study characterized and compared the fecal and oral microbiota from women with early-stage breast cancer (BC), women with ductal carcinoma in situ (DCIS), and healthy women. Fecal and oral samples were collected from newly diagnosed patients prior to any therapy and characterized using 16S rRNA sequencing. Measures of gut microbial alpha diversity were significantly lower in the BC vs healthy cohort. Beta diversity differed significantly between the BC or DCIS and healthy groups, and several differentially abundant taxa were identified. Clustering (non-negative matrix factorization) of the gut microbiota identified five bacterial guilds dominated by Prevotella, Enterobacteriaceae, Akkermansia, Clostridiales, or Bacteroides. The Bacteroides and Enterobacteriaceae guilds were significantly more abundant in the BC cohort compared to healthy controls, whereas the Clostridiales guild was more abundant in the healthy group. Finally, prediction of functional pathways identified 23 pathways that differed between the BC and healthy gut microbiota including lipopolysaccharide biosynthesis, glycan biosynthesis and metabolism, lipid metabolism, and sphingolipid metabolism. In contrast to the gut microbiomes, there were no significant differences in alpha or beta diversity in the oral microbiomes, and very few differentially abundant taxa were observed. Non-negative matrix factorization analysis of the oral microbiota samples identified seven guilds dominated by Veillonella, Prevotella, Gemellaceae, Haemophilus, Neisseria, Propionibacterium, and Streptococcus; however, none of these guilds were differentially associated with the different cohorts. Our results suggest that alterations in the gut microbiota may provide the basis for interventions targeting the gut microbiome to improve treatment outcomes and long-term prognosis.IMPORTANCEEmerging evidence suggests that the gut microbiota may play a role in breast cancer. Few studies have evaluated both the gut and oral microbiomes in women with breast cancer (BC), and none have characterized these microbiomes in women with ductal carcinoma in situ (DCIS). We surveyed the gut and oral microbiomes from women with BC or DCIS and healthy women and identified compositional and functional features of the gut microbiota that differed between these cohorts. In contrast, very few differential features were identified in the oral microbiota. Understanding the role of gut bacteria in BC and DCIS may open up new opportunities for the development of novel markers for early detection (or markers of susceptibility) as well as new strategies for prevention and/or treatment.